Exploring the association of vitamin B12 deficiency and dental health in older adults - Hung, Man; Mohajeri, Amir; Marx, Jacob; Ward, Corban; Lipsky, Martin S. (Frontiers in Nutrition, 2025)
BackgroundVitamin B12 plays a crucial role in overall health, yet its impact on dental health, particularly dental caries, remains underexplored. Older adults are at an increased risk of vitamin B12 deficiency and dental disease, but the relationship between these two factors is not well understood. This study examines the association between serum vitamin B12 levels and dental health in older adults using data from the NHANES 2011–2014 cycles.MethodsA cross-sectional analysis was conducted using NHANES data from 1,907 participants aged 65 and older. Serum vitamin B12 levels were categorized as normal (>221 pmol/L), marginal (148–221 pmol/L), and deficient (<148 pmol/L). Dental status was assessed using the Decayed, Missing, and Filled Teeth (DMFT) index based on NHANES dental health examinations. Poisson regression models evaluated associations between vitamin B12 levels and DMFT scores, adjusting for age, sex, race/ethnicity, education, and income.ResultsLower vitamin B12 levels were significantly associated with higher DMFT scores (p < 0.05). Participants with marginal and deficient vitamin B12 levels exhibited increased DMFT scores compared to those with normal vitamin B12 levels, and these differences persisted after adjusting for demographic and socioeconomic factors. The findings suggest that inadequate vitamin B12 status may contribute to a greater cumulative burden of dental disease in older adults.ConclusionThese findings suggest that vitamin B12 deficiency may contribute to a greater lifetime burden of dental disease in older adults. Further research is needed to explore causal mechanisms and assess whether vitamin B12 supplementation could be a preventive measure for maintaining dental health in aging populations.